Evaluation of teaching and learning delivery modes in arts : final project report. - Peterson, Jim; Ha Phan, Le; Piscioneri, Matthew; Hlavac, Jim (Australian Learning and Teaching Council, 2009)
The major aim of the project was to trial and evaluate the efficacy of three teaching and learning resource delivery modes - online (WebCT), physical digital media (DVD) and hard copy (paper) particularly in relation to learning outcomes. In addition the project developed, implemented and assessed student approaches to pre-lecture reading requirements through the minimalist reading model [MiRM] and integrated language and learning support [ILLS] resources.